Pengaruh Manajemen Kelas terhadap Kedisiplinan Siswa Kelas VIII di SMP Negeri 2 Sangatta Utara - Ratih Fatonah; Faelasup Faelasup; Miftakhul Rizal Mubaidillah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to determine the extent of the influence of classroom management on the discipline of eighth-grade students at SMP Negeri 2 Sangatta Utara. This study uses a quantitative research method with a field research type. The determination of the sample size is done using the proportional random sampling formula with a percentage of 50%, resulting in a sample of 98 respondents. The data collection technique employs a questionnaire technique. The results of the first hypothesis testing using the t-test showed a calculated t-value of 5.482. Since this value is greater than the table value (5.482 < 1.984), it is concluded that the classroom management variable has a significant effect on student discipline on a partial basis. In the second data analysis using the F-test, a F-value of 30.050 was obtained, which is greater than the table value of 3.94, with a significant F-value of 0.001, which is smaller than the alpha value of 0.05, thus Ha is accepted. There is a positive influence of Classroom Management on the discipline of eighth-grade students at SMP Negeri 2 Sangatta Utara. The results of the tested determination coefficient formula showed an r square value of 0.238 or 23.8%, which means that the contribution of the Classroom Management variable is 23.8%, which is considered low, while the remaining 76.2% is influenced by other factors outside the variables in this study.